ANALYSIS OF INFANT MORTALITY IN THE WORKING AREA OF NORTH MUSI RAWAS REGENCY IN 2024 - Anggraini, Utari; Chairil Zaman; Dianita Ekawati (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Infant deaths are caused by the top three causes of death, namely LBW, asphyxia and infection. Meanwhile, the highest cause of other neonatal deaths was caused by intrapulmonary complications such as respiratory and cardiovascular disorders. This research aims to determine the picture of infant mortality in the working area of ​​North Musi Rawas Regency in 2024. The design of this research is quantitative with a case control approach. The population in this study were all mothers who gave birth in North Musi Rawas Regency in January 2023. The sample in this study was 99 people, with sampling using case and control 3:1. Namely cases as many as 33 respondents and controls as many as 66 respondents, with the inclusion criteria being willing to become respondents by filling out a consent form, and parents of toddlers. This research was carried out on March 30 - April 29 2024. Primary data was collected by interviews using questionnaires. Bivariate data analysis used the Chi-Square test. The results of the study showed that there was a relationship between birth attendant (p value 0.01), place of delivery (p value 0.002), birth weight (p value 0.006), ANC visits (p value 0.00), and comorbidities (p value 0, 00) with the incidence of infant deaths in the working area of ​​North Musi Rawas Regency in 2024. The most dominant factor in the incidence of infant deaths in the working area of ​​North Musi Rawas Regency in 2024, namely birth weight (p value 0.004) (OR 0.261). The conclusion is that there is a relationship between birth attendants, place of delivery, birth weight, ANC visits and comorbidities. The Health Service should coordinate with the Community Health Center to carry out scheduled posyandu activities.